An Investigation of the Frequency and Duration of a Drive Spoon–Dispersed Water Jet and Its Influence on the Hydraulic Performance of a Large-Volume Irrigation Sprinkler - Pan Tang; Chao Chen (Agronomy, 2022)
The frequency and duration of drive spoon–dispersed water jet directly influence the water distribution pattern and, further, affect water distribution uniformity. A mathematical model for calculating the duration was established, and an experiment was carried out to verify the accuracy of the theory by using high-speed photography (HSP) technique. Another important component of the investigation was the influence of frequency and duration on the water distribution pattern and water distribution uniformity. The results showed that the frequency of drive spoon–dispersed water jet increased and the duration time decreased with increased working pressure and decreased distance between counterweight-installed position and rotation axis. The calculated values of the theory were greater than the measured values. Differences between the measured and predicted values decreased with increased working pressure, and the average difference decreased to 2.98% when the working pressure increased to 0.40 MPa. The application rates within 1–13 m improved and increased about 50% by decreasing the distance from 135 mm to 80 mm. The maximum application rates decreased from 10.3 to 9.2 mm h−1, 9.5 to 8.8 mm h−1, and 8.4 to 7.9 mm h−1 with a working pressure of 0.30, 0.35, and 0.40 MPa, respectively. The Christiansen’s uniformity coefficient (CU) values decreased by increasing the distance between the counterweight and the rotation axis. The maximum CU values were obtained at the spacing coefficient of 1.2, 1.2, and 1.1 for 0.30, 0.35, and 0.40 MPa, respectively. By decreasing the distance from 135 mm to 80 mm, the maximum CU values increased from 58.96% to 75.1%, 68.85% to 80.1%, and 72.46% to 82.17% for 0.30, 0.35, and 0.40 MPa, respectively.